(untitled) (Baghdad Science Journal, 2025)
This study was conducted to evaluate the efficacy of Saccharomyces cerevesiae as a growth promoting agent in tomato. Soaking the seeds in yeast suspension at 5 g/L for 12h increased germination percentage, root length, root fresh and dry weight, plant height, foliage fresh and dry weight, attained 88.5% ; 8.1 cm ; 84.3 mg ; 7.03 mg ; 10.75 cm ; 839 mg and 37.75 mg compared with 80% ; 5.33 cm ; 39 mg ; 4.8 mg ; 7.35 cm ; 608 mg and 25.5 mg in seedlings grown from non treated seeds respectively. Similar results were obtained with seedling from seeds soaked in S. cerevesiae filtrate for 12 hrs. with values of 77.5% ; 6.875 cm ; 91.5 mg ; 7.5 mg ; 9.5 cm ; 777 mg and 40.35 mg compared to 66% ; 5.8 cm ; 57.7 mg ; 5.03 mg ; 5.9 cm ; 493 mg and 27.28 mg in control (non treated seeds) for the same above criteria respectively. Watering the soil together with spraying the foliar parts with S. cerevesiae suspension at 5 and 8 g/L were found to be more effective than watering and spraying the plants separately in plant growth stimulation under plastic house conditions. The leaf contents of chlorophyll attained to 60.4 and 61.17 SPAD unit compared with 50.37 SPAD units in control respectively and leaf area reached to 3124 and 3119 cm2 / plant compared with 1904 cm2 / plant in control for the two concentrations respectively. The treatment induced also an increasing in plant high ; fresh and dry weights which attained 222 cm ; 223.3 cm ; 1485.7 g ; 1489 g ; 340.7 g ; 341.7 compared to 186 cm ; 1169.3 g ; 286 g in control for the two concentrations respectively. Similar increasing in root length , root fresh and dry weight and yields which attained 30.33 cm ; 30.7 cm ; 61 g ; 61.33 g ; 14.33 g ; 14.33 g ; 6.9 kg / plant and 6.95 kg / plant compared to 24.13 cm ; 46 g ; 10 g and 4.22 kg / plant in control , were found. The stimulations of plant growth criteria was found in concomitance with increase of N ; P and K in treated plant leaves which reached 2.293 ; 2.3 ; 0.4007 ; 0.402 ; 0.5506 and 0.5723% compared to 1.458 ; 0.2283 and 0.1226% in control for the two concentrations respectively . In addition increasing in total solid soluble material (TSS), 5.2 and 5.2023% compared to 3.867% in control treatment were observed.